IMPLEMENTASI KEBIJAKAN PERATURAN PEMERINTAH NOMOR 53 TAHUN 2010 TENTANG KEDISIPLINAN APARATUR SIPIL NEGARA DI SEKRETARIAT DAERAH KABUPATEN ENREKANG - Samsul Alam (FISIP Universitas Muhammadiyah Sidenreng Rappang, 2018)
This research was conducted in the Regional Secretariat enrekang with the goal to determine the application of the discipline policy implementation based on number 53 in 2010. Data collection techniques used were observation and questionnaires/questionnaire respondents. The population of 98 people and the sample that is the entire population of 98 people. Data analysis technique used is quantitative descriptive.The results showed that : The application of the discipline policy implementation of PP No. 53 of 2010 on Regional Secretariat ASN Enrekang. Factors of discipline: a). punctuality is at a score of 3,32 (66,53%) or good category, b). office equipment with both being in a score of 4,07 (81,42%) or excellent category, c). responsibility is on the score 3,86 (77,34%) or good category, d). observance of the rules that are in a score 3,74 (74,89%) or good category. And indicators of discipline, namely : a). The ability to be on the score of 3,83 (76,73%) or good category, b). exemplary leader currently on a score of 3,88 (77,75%) or good category, c). remuneration is at a score of 3,93 (78,77%) or good category, d). justice was on the score of 4,06 (81,22%) or excellent category, e). supervision is at a score of 3,85 (77,14%) or good category, f). sanctions or relationships that are in a score of 4,02 (80,40%) or good category, g). assertiveness was on the score of 4,08 (81,63%) or excellent category, h). relations are at a score of 3,90 (78,16%) or good category.